(untitled) (Pakistan Journal of Science, 2022)
Uniaxial compressive strength (UCS) of intact rocks is a major consideration in rock mechanics study for civil and mining projects. UCS direct testing is expensive, time consuming and it involves preparation of rock samples. Indirect tests are relatively cheaper, faster, and are convenient to perform in the laboratory and at site. This work presents the development of possible empirical relations between UCS values determined by direct and indirect testing methods including Point Load Index and Sonic Velocity for dolerite. A review of various correlations established for UCS versus point load index and UCS versus sonic wave velocity for different rocks by various researchers have also been presented.